Exploring potential benefits and challenges of touch screens on the flight deck - Avsar, Hüseyin (2017)
As the avionics industry is seeking to introduce touch screens into most flight decks, it is vital to understand the interactional challenges and benefits of doing so. The potential benefits and challenges of touch screen technology on flight decks was investigated by means of a variety of qualitative and quantitative research methods (mixed methods approach). A number of research questions are addressed, which have been iteratively developed from the literature, interviews with avionics experts and pilots. This work presents one field study, two lab studies, one observational study, one simulation study and one comparative user study, all investigating various factors/variables that could affect touch screen usability on the flight deck.